Fungsi Humas Pemerintah Daerah Kota Serang dalam Memperkuat Komunikasi Kebijakan Pengelolaan Sampah di Kelurahan Cilowong - Muhammad Lutfi Zaini; Nani Nurani Muksin (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
In handling waste management, the Serang City Environmental Service facing several problems, especially in communication between governments and society. This can be seen from the low level of participation and understanding community about the importance of their role in waste management and protecting the environment, as well as ongoing complaints from related communities waste management. This research aims to find out and analyze the function of local government in strengthening management policy communication waste at the Environmental Service, policy communication carried out by Serang City Environmental Service, problems and obstacles faced by the Department Environment in strengthening policy communication. The theory that used in this research is the theory of Government Relations and Communication Policy. This research uses a qualitative approach with types descriptive research. Data collection methods were collected through interviews in depth and documentation. The research results show that 1. Giving information to the public, DLH Serang City conveyed about waste management through education and campaigns. 2. Do persuasion for changing people's attitudes and behavior, through campaigns and involving community leaders, to encourage awareness and participation public. 3. Align the attitudes and actions of the institution with the community or vice versa, carried out through discussion forums and surveys. 4. Transmission, DLH The city of Serang succeeded in transmitting information using various communication channels, such as social media, official websites, and socialization direct. 5. Clarity, Serang City DLH uses simple language and Illustrations help in conveying information to create understanding better for society. 6. Consistency, Serang City DLH maintains consistency between policies and messages through dedicated teams.